63 numaralı mühimme defteri (995-996/ 1587-1588) - Kar, Serdar (My University, 2002)
Osmanlı Devleti merkez teşkilâtının en mühim müessesesi olan Divân-ı Hümâyûn, devletin siyasî, askerî, malî işleriyle meşgul olur, her türlü dava ve şikâyetlere bakardı. Divân-ı Hümâyûn'da alınan kararlar, ferman, berat ve hükümlerin nakil kısmı Divân-ı Hümâyûn sicilleri olarak da bilinen mühimme defterlerine kaydedilirdi. Özellikle padişaha ait belgelerden birisi olan ferman sefer açılması, asker sevki, vergi, vs. devlet işlerine dair, doğrudan doğruya Divân-ı Hümâyûn'un kararı ve padişahın emri üzerine hazırlanıp ilgili şahıslara gönderilirdi. Konumuz olan mühimme defterleri Divân-ı Hümâyûn kalemlerinden Beylikçi veya Divân Kalemi diye adlandırılan kalem dairesinde mühimmenüvisân denilen kâtipler tarafından kaleme alınır ve hıfzedilirdi. Kaleme alınan bu mühimme defterlerindeki hükümlerin üstlerinde, hükümlerin nasıl meydana geldiği, ne gibi muamele gördüğü veya cevabın mahiyeti ile ilgili olan ve zamanla, belki de Reisü'l-küttab'ın yönlendirmesine göre değişiklik gösteren çeşitli kayıtlar mevcuttur. Bu kayıtlar Osmanlı bürokrasisi bakımından olduğu kadar diplomatiği açısından da ehemmiyet arz etmektedir. Tarih araştırıcılarının istifadesine sunduğumuz 1587-1588 yıllarına ait 63 Numaralı Mühimme Defteri de yukarıda belirttiğimiz husûsiyetleri haiz olup devrinin siyasî, askerî, malî, içtimaî vs. hadiseleri hakkında birçok malumatı muhtevidir. Defterimizin kaleme alındığı yıllar Osmanlı Devleti'nin içerde birtakım eşkıyanın bozgunculuk faaliyetleri ile ve Alevi ayaklanmalarıyla; dışarda da İran ile devam etmekte olan savaşla ve Gürcistan üzerine düzenlenen sefer ile meşgul olduğu dönemdir. İran, Osmanlı Devleti aleyhine bir taraftan Avrupa devletleriyle iyi ilişkiler kurmakta, diğer taraftan Anadolu içerisinde kendisine taraftar kıldığı Aleviler'i isyana teşvik etmektedir. Bu durum karşısında Osmanlı Devleti ise, bir ara İran içerisinde baş gösteren taht kavgalarını fırsat bilerek İran üzerine sefer açmaktadır. Fırsat buldukça Osmanlı aleyhine isyana tevessül eden Gürcüler üzerine de sefer açılıp onlara ders vermeye çalışılırken bir yandan da Ruslar'a gözdağı verilmeye uğraşılmaktadır.

The Royal state council Divân-ı Hümâyûn which is the most important body of the central organization of Ottoman Empire, was involved in political, military and financial affairs of the state. And take care of any actions and complaints therewith. The decrees resolved with The Royal state council Divân-ı Hümâyûn, the royal orders ferman, royal warrant and provisions were recorded with the ledger books called mühimme which was also known as the registration of The Royal state council Divân-ı Hümâyûn. Particulary the royal orders ferman, which was one of the exclusive documents of the sultans, used to be issued based on the direct resolutions of The Royal state council Divân-ı Hümâyûn, or otherwise the sultan's himself. For the matters particularly related to the major state affairs such as; declaration of wars, mobilization, taxes ete, and relayed to the authorities concerned accordingly. The ledger books, which constitute the subject matters of this study, were used to be written and kept by the royal clerks called mühimmenüvisân who as a matter of fact were employed in the royal clerk's office Beylikçi (chancery office) or Divân Kalemi (the office of Secretary of State Council). Over the provisions included in these ledger books called mühimme are various notes showing many changes either related to the time, or the answer backs and how it was treated by the office and the process of the provision itself, probably including the direction of the Reisü'l-küttab (Minister of foreign Affairs). Such notes and records are important in terms of Ottoman Bureaucracy and diplomacy. The ledger books called mühimme with the reference no.63 of the years between 1587-1588 which we submitted to the benefit of the history researchers, has the above mentioned characteristics and includes many valuable information related to the state political, military, financial, social etc. Affairs of its time, the years wherethe said ledger book called mühimme was kept falls under an era where many defeatism activities were lead by many outlaws within the Ottoman country while the state has been involved in dealing with Alawi rebellions and riots, inside and the Iran war outside including the war which was continuing with Georgia and the preparation of further campaign therewith.Iran was involved in many treaties with the European Countries against Ottomans, while provoking the Alawis whom they made partisans for Iran for rebellion against Ottpmans within the Anatolian land. In this case, The Ottoman State made a campaign over Iran when the internal conflict in Iran appeared for the transfer of the power amongst the Iranian royalists. The Georgians who used to attempt for riots against Ottomans were also taken as the military target by the Ottoman State and the army was marched on the Georgians to give them a lesson that they deserved, and to intimidate the Russia by this opportunity.
Keywords: Tarih Yeniçağ